2003
DOI: 10.1111/j.1744-7348.2003.tb00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of parathion‐methyl to cells, akinetes and heterocysts of the cyanobacterium Cylindrospermum, sp. and the probit analysis of toxicity

Abstract: The toxicity of a commercial formulation of the insecticide parathion-methyl to the N 2 -fixing filamentous cyanobacterium (blue-green alga) Cylindrospermum sp. was studied. A concentration of parathion-methyl of 0.5 ppm caused growth increase in liquid growth media. The minimum inhibitory concentration of parathion-methyl for both types (N 2 -fixing and nitrate supplemented) of liquid and solid media was 1.0 ppm. LC 50 values were: 4.4 ppm (liquid, N 2 -fixing), 5.5 ppm (liquid, nitrate supplemented), 3.3 ppm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…The effect of two PAHS on microalgal populations has been considered to be inhibitory at high doses (Panigrahi et al, 2003). Data obtained in the present investigation revealed that both the strains were more susceptible to PAHS.…”
Section: Discussionsupporting
confidence: 60%
“…The effect of two PAHS on microalgal populations has been considered to be inhibitory at high doses (Panigrahi et al, 2003). Data obtained in the present investigation revealed that both the strains were more susceptible to PAHS.…”
Section: Discussionsupporting
confidence: 60%
“…Cellular dehydrogenase activity determined by TTC-test, a universal index to evaluate cell viability (Shiu and Lee 2005;Panigrahi et al 2003), was shown to dramatically decrease when M. aeruginosa NIES-843 was under the stress of a CMK loading of 80 and 160 mg/l, and cellular dehydrogenase activities were decreased to the levels of lower than detectable limits on 12th and 8th day, respectively. These results indicated that cell mortality of M. aeruginosa occurred after flocculated by CMK.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, computation of SE as well as 95% CL is not suggested, which would simplify both of the Spearman-Karber method and the original probit transformation method. Moreover, two additional probit-method-computed values, LC 25 and LC 75 lend themselves to an introspecting facility on values of LC 50 , MIC and HPC of a dataset (Panigrahi et al, 2003); eventually, the redundancy of computation of CL for LC 50 value gets confirmed.…”
Section: Methods IVmentioning
confidence: 99%
“…The usual response types include: (a) promoting-effect concentration (PEC) (e.g., growth-enhancing effect, when growth is the parameter); (b) no-observed-effect concentration (NOEC); (c) least-observed-effect concentration (LOEC), minimum inhibitory concentration (MIC), or threshold concentration, when the test chemical is incapable of producing the effect studied below a critical concentration; (d) highest-permissive concentration (HPC) or optimum concentration, when the effect is maximum at a particular level of the test chemical; and (e) minimum bactericidal concentration (MBC) (OECD, 1981). Moreover, in toxicology of test chemical for microbes, investigators often determine the MIC, lethal concentration 50 (LC 50 ) or effective concentration 50 (EC 50 ), the HPC and lethal concentration 100 (LC 100 ) or MBC, as routine expressions (Wardlaw, 1985;Panigrahi et al, 2003). Further, in toxicology a toxic substance may be tested to determine its toxicity range against any system; and in pharmacology and immunology protective efficacy of drugs and vaccines is determined in cell cultures in vitro, as well as in animal-systems.…”
Section: Introductionmentioning
confidence: 99%